Frequency and Causes of Hypotonia in Neonatal Period with the Gestational Age of More Than 36 Weeks in NICU of Mofid Children Hospital, Tehran, Iran During 2012-2014 - SEYED SHAHABI, Nosratollah; FAKHRAEE, Hossain; KAZEMIAN, Mohammad; AFJEH, Abolfazl; FALLAHI, Minoo; SHARIATI, Maryam; GORJI, Fatemeh (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Seyed Shahabi N, Fakhraee H, Kazemian M, Afjeh A, Fallahi M, Shariati M, Gorji F. Frequency and Causes of Hypotonia in Neonatal Period with the Gestational Age of More Than 36 Weeks in NICU of Mofid Children Hospital, Tehran, Iran During 2012-2014. Iran J Child Neurol. Winter 2017; 11(1):43-49. Abstract Objective Hypotonia is a serious neurologic problem in neonatal period. Although hypotonia is a nonspecific clinical finding but it is the most common motor disorder in the newborn. The objective of this study was to determine the frequency of neonatal hypotonia then to ascertain of the most common causes. Materials & Methods This cross –sectional prospective study was carried out on the 3281 term infants hospitalized in conventional and NICU of Mofid Children Hospital, Tehran, Iran during 2012-2014. Diagnosis was made by history, physical & neurological examination and accessible diagnostic tests. Results Fifty nine hypotonic neonates were identified, forty seven (79.66%) had central hypotonia (Hypoxic ischemic encephalopathy (n= 2), other causes of encephalopathy (n=2), intracranial hemorrhage (n=4), CNS abnormalities (n= 7), chromosomal disorders (n=4), syndromic–nonsyndromic (n=8), and metabolic diseases (n=8). Peripheral hypotonic recognized in 6 infants (10.17%); spinal muscular atrophy (n= 1), and myopathy (n= 5). Six cases (10.17%) remained unclassified. Twelve infants had transient hypotonia. In final study, 18 of 59 infants (30%) died, nearly 90% before one year of age. Twenty-eight (47%) infants found developmental disorders and only 13 (22%) infants achieved normal development in their follow up. Conclusion Neonatal hypotonia is a common event in neonatal period. A majority of diagnosis is obtained by history and physical examination. Neuroimaging, genetic and metabolic tests were also important in diagnosis. Genetic, syndromic–nonsyndromic, and metabolic disorders were the most causes of neonatal hypotonia. References 1.Miller VS, Delgado M, Iannaccone ST. Neonatal hypotonia Seminar in neurology 1993; 13 (1):73-83. 2. Laugal V, Cossee M, MJ. de Saint –Martin A, Echaniz- Laguna A, Mandel JL, Astruc D, Messer FMJ. Diagnostic approach to neonatal hypotonia: retrospective study on144neonates.Eur J Pediatr 2008; 167:517-523. 3. Birdi K, Prasad C, Chodirker B, Chudly AE, The floppy infant: retrospective analysis of clinical experience (1990-2000) in a tertiary care facility. J Chlid Neurol 2005; 20: 803-808. 4. Johnston HM.The floppy weak infant revisited. Brain Dev 2003; 25:55-58. 5. Crawford TO. Clinical Evaluation of the Floppy infant. Pediatric Annal 1992;16:348-354. 6. Richer LP, Shevell MI, Miller SP. Diagnostic profile of neonatal hypotonia; An 11 year study. Peditric Neurol 2001; 25:32-37. 7. Paro–Panjan D. Congenital hypotonia is there an algorithm. J Child Neurology 2004;19 (6):439-442. 8. Griggs RC, Mendell JR, Miller RG. Cngenital myopathies.in: Evaluation and treatment of myopathies. Philadelphia:FA Davis C; 1995:211-46 9. Nada Zadeh and Louanne Hudgings. The Genetic Approach to hypotonia in the neonate. NeoReviews 2009; 10; e600-e607. 10. Bodenstiener JB. The evaluation of the hypotonic infant Seminar in PediatricNeurology 2008;15:10-20. 11. Dubowitz V. Thomas NH. The natural history of type 1(severe) spinal muscular dystrophy. Neuromuscular Disord. 1994;4:497-50212. 12. Jimenez E, Garcia – Cazoria A, Colomer J, Nascimento A, Ieiondo M, Compistol J. Hypotonia in the neonatal period: 12 years experience.[Article in Spanish] Rev Neurol 2013 Jan16:56 (2):72-8.